Impact of Exchange and Communications Technology on Firm Performance: The Mediation Effect of Supply Chain Capabilities (Global Journal of Management and Business Research, 2022)
Network-enabled enterprise systems called inter-organizational systems use IOS go beyond the walls of an organization allowing partners in the supply chain to collaborate better by exchanging business information in real time As a result the study Case Study Sudan Food Industry examined the Mediating Role of Supply Chain Management Capabilities on the Relationship between Inter-Organizational System Use on Firm Performance with the purposeful participation of 450 participants to whom the questionnaire was addressed The information was then gathered from the supply chain and production management at the Sudanese food processing industry The data was then coded using SPSS and AMOS 26 After ensuring normality validity and reliability a descriptive analysis was conducted and variable correlation was examined Path analysis was formerly used to test hypotheses The findings of the study reveal IOS have a positive and significant impact on SCM capabilities also SCM capabilities mediating the relationship between IOS and Performance
Keywords: inter-organizational systems; supply chain responsiveness; supply chain integration